Design and development of fretting fatigue test apparatus - Arora, Prithvi Raj; M. S. D., Jacob; Elsadig Mahdi, Ahmed; Mohd. Sapuan, Salit; M., Saleem (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/